Aplikasi Steganography Pdf To Image Dengan Metode Spread Spectrum - Marlina; wahyuni, Nurrahmi (Fakultas Teknik Universitas Muhammadiyah Parepare, 2022)
Therefore we need a way to secure the data / information to be sent. Steganography is a technique that can be used to secure data/information. Steganography is a technique used to hide messages in a medium such as images, audio and video. Based on these problems, the authors make a steganography application that can be used to hide PDF files into image media (cover image), and can be used to retrieve PDF from images that have been inserted (Stegano Image). The image media used as input (cover image) is in JPG format. The algorithm used to hide and retrieve PDFs and from images is Spread Spectrum. As for testing the system, the results are in accordance with what has been targeted, the results show that encryption and decryption are carried out by testing the table 5 times.